Dystonia: an update on phenomenology, classification, pathogenesis and treatment - Balint, Bettina; Bhatia, Kailash P. (Current opinion in neurology, 2014)
Purpose of review: This article will highlight recent advances in dystonia with focus on clinical aspects such as the new classification, syndromic approach, new gene discoveries and genotype-phenotype correlations. Broadening of phenotype of some of the previously described hereditary dystonias and environmental risk factors and trends in treatment will be covered. Recent findings: Based on phenomenology, a new consensus update on the definition, phenomenology and classification of dystonia and a syndromic approach to guide diagnosis have been proposed. Terminology has changed and ‘isolated dystonia’ is used wherein dystonia is the only motor feature apart from tremor, and the previously called heredodegenerative dystonias and dystonia plus syndromes are now subsumed under ‘combined dystonia’. The recently discovered genes ANO3, GNAL and CIZ1 appear not to be a common cause of adult-onset cervical dystonia. Clinical and genetic heterogeneity underlie myoclonus-dystonia, dopa-responsive dystonia and deafness-dystonia syndrome. ALS2 gene mutations are a newly recognized cause for combined dystonia. The phenotypic and genotypic spectra of ATP1A3 mutations have considerably broadened. Two new genome-wide association studies identified new candidate genes. A retrospective analysis suggested complicated vaginal delivery as a modifying risk factor in DYT1. Recent studies confirm lasting therapeutic effects of deep brain stimulation in isolated dystonia, good treatment response in myoclonus-dystonia, and suggest that early treatment correlates with a better outcome. - Summary: Phenotypic classification continues to be important to recognize particular forms of dystonia and this includes syndromic associations. There are a number of genes underlying isolated or combined dystonia and there will be further new discoveries with the advances in genetic technologies such as exome and whole-genome sequencing. The identification of new genes will facilitate better elucidation of pathogenetic mechanisms and possible corrective therapies.
Gesehen am 24.07.2020